Assessment of Sleep Quality, Daytime Sleepiness, and Depression among Emergency Physicians Working in Shifts - Sulaiman Alhifzi; Aseel Al-Ghonimy; Malak Al Aboudi; Rawan Al Abdullah; Awad Olaish; Ahmed S BaHammam (Wolters Kluwer Medknow Publications, 2018)
Background: Around-the-clock provision of medical care is needed particularly in acute care areas. Emergency physicians are constantly affected by rotating shifts. Therefore, we conducted this study to assess the sleep quality, daytime sleepiness, and depression among emergency physicians. Methods: This study is a cross-sectional case-control study. Participants were divided into two groups; primary participants were 68 emergency physicians working in a shift work system and the controls were 69 family medicine physicians working in a fixed daytime shift. A self-administered questionnaire was filled by all participants that comprised the Epworth Sleepiness Scale (ESS), the Pittsburgh Sleep Quality Index (PSQI), and the Beck Depression Inventory. Results: Based on the PSQI, around 83.8% of emergency physicians had poor sleep quality, compared to 50.7% in the control group. Daytime sleepiness (ESS >10) was significantly higher in the emergency physicians in comparison to the control group (41.2% vs. 14.5%). A strong correlation was found between poor sleep quality and depression in emergency physicians (r = 0.437, P = 0.001). Conclusion: Emergency physicians working in a shift work system had a significant increase in daytime sleepiness and poor sleep quality. Depressive symptoms were noted among emergency physicians suffering from poor sleep quality.